Dielectric permittivity of composite polymer materials based on polyethylene containing copper nanoparticles (Acta Education, 2025)
Two types of composite materials containing copper micro- and nanoparticles in a polyethylene matrix have been created and studied. The static dielectric permittivity of polyethylene containing copper nano- and microparticles was measured near the percolation threshold.  It has been established that below this threshold, discrepancies between experimental data and predictions from modern theory of heterogeneous systems are observed. It has been found that in polyethylene-based composites with copper nanoparticles, an additional contribution to dielectric permittivity is observed in the region below the percolation threshold. The reasons for this effect are considered, taking into account the spatial structure of the material within the framework of the model proposed by Balberg and his co-authors for composite systems